Cross‐Dehydrogenative Coupling of Tertiary Amines and Terminal Alkynes Catalyzed by Copper Nanoparticles on Zeolite. Issue 16 (18th November 2015) - Alonso, Francisco; Arroyo, Adrián; Martín‐García, Iris; Moglie, Yanina
Abstract: A wide range of catalysts based on supported copper nanoparticles have been prepared and tested in the cross‐dehydrogenative coupling of tertiary amines and terminal alkynes. Copper nanoparticles on zeolite Y were found to be the most effective catalyst in the presence of tert ‐butyl hydroperoxide as the oxidant. Contrary to the previously reported methodologies involving copper catalysts, reactions have been accomplished without the need of an inert atmosphere and in the absence of solvent, using 1.5 mol% catalyst. A variety of tertiary amines, including aromatic, benzylic and aliphatic ones, have been coupled with both aromatic and aliphatic alkynes to furnish the corresponding propargylamines in moderate‐to‐excellent yields. The procedure has been successfully scaled‐up to 12 mmol with a high conversion (93%). Moreover, the catalyst has been reused in seven cycles maintaining a good performance. Its catalytic activity has been compared with that of an array of commercial copper catalysts, being superior as regards the conversion and minimizing the alkyne homocoupling as a side reaction. The negative filtration test points to a heterogeneous nature of the process. Based on compelling experimental evidence, a novel reaction mechanism has been delineated which outlines the essential role of free radicals and the couple copper(I)/copper(II). Abstract :